2009
DOI: 10.1016/j.icheatmasstransfer.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Application of high porosity metal foams as air-cooled heat exchangers to high heat load removal systems

Abstract: A numerical study has been conducted to investigate the fluid flow and heat transfer of an air-cooled metal foam heat exchanger under the high speed laminar jet confined by two parallel walls for which the range of the Reynolds number is 600-1000. Two independent numerical solvers were used and crossvalidated being a FORTRAN code and the commercially available software CFD-ACE. The effects of local thermal non-equilibrium, thermal dispersion, porosity, and pore density on the heat transfer augmentation are exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…Similar findings were reported by Calmidi and Mahajan [37]. Ejlali et al [57] conducted a numerical study to investigate the fluid flow and heat transfer of an air-cooled metal foam heat exchanger under a high speed laminar jet confined by two parallel walls for which the range of the Reynolds number is 16 600-1000. They considered two different metal foam heat exchangers samples, intended for use in a geothermal power plant, and compared the results to a reference pin fin heat sink.…”
Section: Liquid-to-gas Heat Exchangerssupporting
confidence: 69%
“…Similar findings were reported by Calmidi and Mahajan [37]. Ejlali et al [57] conducted a numerical study to investigate the fluid flow and heat transfer of an air-cooled metal foam heat exchanger under a high speed laminar jet confined by two parallel walls for which the range of the Reynolds number is 16 600-1000. They considered two different metal foam heat exchangers samples, intended for use in a geothermal power plant, and compared the results to a reference pin fin heat sink.…”
Section: Liquid-to-gas Heat Exchangerssupporting
confidence: 69%
“…Among them, metal foams were used as alternative to find extended surfaces utilized in removing heat from geothermal power plants, where metal foam heat exchangers offer superior thermal performance compared to conventional finned surfaces, at no extra cost resulting from the pressure drop and/or material weight [13]. In this regard, wrapping a thin layer of foam around the surfaces of tubes was proposed to enhance the heat transferred from/to them with little increase in the pressure drop produced [14][15][16].…”
Section: Applicationsmentioning
confidence: 99%
“…Some typical examples of employing augmented fin geometries amid plate fin heat sinks were proposed. For instance, studies from Yu et al [7], Yang and Peng [8] (plate + pin fin combination), Yang et al [9] (louver or slit fin), Kim et al [10] (triangular or reversetrapezodial fin), Yang et al [11,12] (vortex generator), Ejlali et al [13] (metal foam) and Wang et al [14] (Cannelure Fin) in their compact plate fin heat sink had demonstrated various fin designs applicable to certain applications. Notice that the foregoing studies employed various heat transfer augmentation mechanisms such as boundary layer reseating, swirled flow, and geometrical non-uniformity to promote heat transfer for certain specific conditions.…”
Section: List Of Symbolsmentioning
confidence: 99%